Antihepatotoxic effect of Elephantopus scaber L. on carbon tetrachloride-induced hepatotoxicity in rats - Batu, Ganga Rao; Venkateswara Rao, Y; Praneeth Dasari, V S (Recent Research in Science and Technology, 2012)
Elephantopus scaber was used in folk medicine in several countries to treat different diseases. Liver diseases are major World wise health Problems. The Present aim of the study was evaluate The Antihepatotoxic effects of different fractions of Elephantopus scaber against Carbon tetrachloride (CCl4) induced hepatic damage in Rats. All the fractions were given orally in different doses (125mg/kg, 250mg/kg, 500mg/kg). The Antihepatotoxic effect was assessed by measuring serum parameters like aspertate transaminase (AST), alanine transaminase (ALT), Alkaline Phospatase (ALP) and total bilurubin. All the fractions of Elephantopus scaber showed Antihepatotoxic effect.The ethanol fraction was shows significant percentage protection than compared to other fractions. Therefore, our study supports the isolation and use of active constituents from Ethanol fraction of Elephantopus scaber in treating of liver disease.